PERAN KECERDASAN BUATAN (AI) DALAM PEMBELAJARAN MANAJEMEN MUTU: LITERATURE REVIEW - Nurhidayati, Rina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the role of AI in co-management learning through qualitative descriptive literature observation methods. The journals were collected from various academic sources from 2020–2025 with relevant keywords such as AI in education quality management and technology-enhanced learning. The results of the study indicate that artificial intelligence improves the personalization of learning and the effectiveness of education management. AI enables automation of administrative tasks, data-driven decision making, and learning that is tailored to individual needs. In addition, the results show that artificial intelligence helps improve education through enjoyable learning experiences and more effective management systems, especially in contemporary learning environments such as the Metaverse. However, there are several obstacles that hinder its implementation, including infrastructure limitations, lack of teacher expertise, ethical issues, and data privacy. As a result, AI can help transform education strategically. However, to achieve an inclusive, effective, and sustainable education system, comprehensive policies and preparations are needed.